Use of homeopathy in feeding piglets as an alternative to reduce fighting behavior in the nursery phase: effects on production and hematological, metabolic, and oxidative variables - Zago I.* (2024)
© The Author(s), under exclusive licence to Springer-Verlag London Ltd., part of Springer Nature 2024.This study aimed to determine whether using a homeopathic agent would improve the behavior, growth performance, redox status, and neuroimmune pathways of the central nervous system in weaned pigs. A total of 108 pigs in the nursery phase were divided into four groups with nine replicates per group (n = 3) as follows: the negative control (NC) group, receiving only the basal diet, the HC2.5 group treated with a conventional and commercial homeopathic at 2.5 kg/t in the basal diet (the vehicle was CaCO3), the HT2.5 group treated with a homeopathic test at 2.5 kg/t in the basal diet (expanded silicate vehicle), and the HT5 group treated with a homeopathic at 5 kg/t in the basal diet (expanded silicate vehicle). It was verified that in the HT5 group, followed by the HC2.5 group, the pigs spent less time standing still compared to the NC group (P = 0.001), and the pigs in the HT2.5 group spent less time sleeping than the NC and HT5 groups (P = 0.024). A higher villus-to-crypt ratio was found in the HT5 group than in others (P = 0.01). In the cerebellum, a lower activity of 5′-nucleotidase/adenosine monophosphate was observed in all groups that received the homeopathic compared to the NC group (P = 0.01). In the cerebral cortex, there was a lower activity of the enzymes NTPDase/ATP, NTPDase/ADP, and 5′-nucleotidase/AMP in all groups that received homeopathic treatment compared to the NC group. During growing, there was greater weight gain in pigs that received the homeopathic concerning NC (P = 0.02), as the pigs had a lower incidence of fighting behavior.